What role does causality play in comprehension of expository teaching materials and do cognitive load and individual differences impact that role? - Vargo, Taylor Leigh (My University, 2025)
This study investigates how cognitive load, causal connections, and individual differences influence comprehension of expository materials, particularly in online learning environments. This study focused on enhancing germane cognitive load by using graphic organizers—diagrams that visually represent concepts and the relationships between them to support student learning of classroom material. Participants engaged with educational content through self-generated and ready-made graphic organizers under explicit or implicit causality conditions and their comprehension for the content were tested across three delays ranging from 1 - 23 days. Results supported the Cognitive Load Hypothesis, revealing that self-generation tasks could hinder learning by imposing high cognitive demands. Explicit causal connections facilitated comprehension, but their effectiveness varied across different sessions, suggesting the importance of encoding accuracy and retrieval timing. Ready-made graphic organizers outperformed self-generated ones, particularly during delayed assessments, which was likely due to poor encoding of the material during the lecture (as evidenced by extremely low accuracy on the self-generated graphic organizer). These findings have significant implications for educational practices, especially in online settings. Instructors are encouraged to incorporate explicit causal structures and provide organized materials to reduce extraneous cognitive load and support retention. The study also highlights the role of individual differences—such as prior knowledge and motivation/engagement—in moderating learning outcomes, underscoring the need for tailored instructional strategies. By deepening our understanding of these factors, educators can better design interventions that enhance student learning and retention.
Keywords: Cognitive load; Causality; Graphic organizers; Mental models; Online learning